[TTK] Reconstructing hydrological variability from testate amoebae analysis in Carpathian peatlands - C. Schnitchen; D. J. Charman; E. Magyari; M. Braun; I. Grigorszky; B. Tóthmérész; M. Molnár; Zs. Szántó; Schnitchen Csaba (1977-) (xxx); Braun Mihály (1966-) (vegyész, analitikus); Grigorszky István (1967-) (biológus); Tóthmérész Béla (1960-) (ökológus) (Journal of Paleolimnology, 2021)
Peatlands offer the potential for high resolution records of water balance over Holocene timescales, yet this potential is under-exploited in many areas of the world. Within Europe, peatlandsare mostly confined to areas north of 55o N, but several areas of southern and eastern Europe contain small peatlands which may be suitable for palaeoclimatic reconstruction. In this paper we test the potential of peatlands in the Carpathian region for deriving quantified estimates of water table changes using testate amoebae analysis. A training set for palaeohydrological reconstruction from testate amoebae assemblages was obtained by collecting surface samples from 13 peatlands, including 9 from Hungary and 4 from Transylvania (Romania). Using a simple measure of mean annual water tables estimated from staining of PVC tape, we found that some peatlands were heavily influenced by runoff and groundwater, and were therefore not suitable as modern analogues of ombrotrophic climatically sensitive sites. The relationship between the testate amoebae assemblages in the modern samples and then environmental variables was explored using CCA. The CCA biplot showed that the most important variables are depth to water table and moisture content, confirming that hydrology is a key control on taxon distribution. pH was a secondary gradient. A transfer function for % moisture and depth to water table was established and applied to fossil assemblages from a sequence from Fenyves-tet}o, Transylvania, Romania. The reconstructed water table shows a number of variations which have parallels with other palaeoclimatic records from Europe and the North Atlantic prominent phases of higher water tables are associated with the periods 8000–8300 cal BP, 3000–2500 cal BP and after 600 cal BP. We suggest that these were periods of particular intensification of westerly airflow which affected easte Europe as well as western and central Europe.